A Review of Current and Pipeline Drugs for Treatment of Melanoma - Nicole Natarelli; Sarah J. Aleman; Isabella M. Mark; Jasmine T. Tran; Sean Kwak; Elizabeth Botto; Shaliz Aflatooni; Michael J. Diaz; Shari R. Lipner (MDPI AG, 2024)
Malignant melanoma is the most aggressive form of skin cancer. Standard treatment options include surgery, radiation therapy, systemic chemotherapy, targeted therapy, and immunotherapy. Combining these modalities often yields better responses. Surgery is suitable for localized cases, sometimes involving lymph node dissection and biopsy, to assess the spread of the disease. Radiation therapy may be sometimes used as a standalone treatment or following surgical excision. Systemic chemotherapy, while having low response rates, is utilized as part of combination treatments or when other methods fail. The development of resistance to systemic chemotherapies and associated side effects have prompted further research and clinical trials for novel approaches. In the case of advanced-stage melanoma, a comprehensive approach may be necessary, incorporating targeted therapies and immunotherapies that demonstrate significant antitumor activity. Targeted therapies, including inhibitors targeting BRAF, MEK, c-KIT, and NRAS, are designed to block the specific molecules responsible for tumor growth. These therapies show promise, particularly in patients with corresponding mutations. Combination therapy, including BRAF and MEK inhibitors, has been evidenced to improve progression-free survival; however, concerns about resistance and cutaneous toxicities highlight the need for close monitoring. Immunotherapies, leveraging tumor-infiltrating lymphocytes and CAR T cells, enhance immune responses. Lifileucel, an FDA-approved tumor-infiltrating lymphocyte therapy, has demonstrated improved response rates in advanced-stage melanoma. Ongoing trials continue to explore the efficacy of CAR T-cell therapy for advanced melanoma. Checkpoint inhibitors targeting CTLA-4 and PD-1 have enhanced outcomes. Emerging IL-2 therapies boost dendritic cells, enhancing anticancer immunity. Oncolytic virus therapy, approved for advanced melanoma, augments treatment efficacy in combination approaches. While immunotherapy has significantly advanced melanoma treatment, its success varies, prompting research into new drugs and factors influencing outcomes. This review provides insights into current melanoma treatments and recent therapeutic advances.